Obesity frequency and related risk factors in primary school children - Ardıç, Cüneyt; Omar, Esma (The European Research Journal, 2019)
Objective: The aim of this study was to determine the obesity and overweight situations and related factors among the children between the ages of 6-11 studying in Rize, Turkey. Methods: The study included 180 pediatric patients (86 girls and 94 boys) applying to our policlinic, who born between 2006 and 2010. The age, height, weight and gender of children and their parents, physical activity status of children, frequency of convenience goods consumption, education and income status of parents and duration of children spent on television were evaluated. Body mass indexes of participants were measured and compared with their socio-demographic characteristics. Results: Obesity was found in 12.2% and overweight was found in 15% of all students participating the study. While a relation was found between being obese or overweight with gender, body mass index of parents, staying more than 2 hours a day in front of television, fast-food consumption and low physicial activity; no relation could be found between the educational status of parents, time of starting supplementary food during infancy and and the duration of total breastfeeding. Conclusions: The increase in frequency of childhood obesity has been particularly important for identifying risk factors associated with obesity and competing with these factors in the early period. Family physicians, the first contact points of the patients, are the most important part of the health system in preventing childhood obesity. A higher prevalence of childhood obesity than other studies in the literature may indicate that obesity will become an increasingly common problem.